2022
DOI: 10.3389/fmicb.2022.912042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clostridium butyricum Supplementation on in vitro Rumen Fermentation and Microbiota With High Grain Substrate Varying With Media pH Levels

Abstract: Clostridium butyricum (C. butyricum) can survive at low pH, and it has been widely used as an alternative to antibiotics for the improvement of feed efficiency and animal health in monogastrics. A recent study suggested that the improved ruminal fermentation with supplementing C. butyricum is may be associated with increasing the abundance of rumen microbiota in Holstein heifers, as ruminal pH plays a key role in rumen microbiota and the probiotics are often active in a dose-dependent manner. The objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The trend of increase of HCW by CB is consistent with the increased LWBS. The increase in LWBS with CB in this study may be due to the fact that the CB can provide metabolites, especially short-chain FA, as an energy source to the digestive enzyme system, thus increase the BW [ 15 ]. The spleen is the largest immune organ in animal body, which can improve the body resistibility and minimize the pathogenic bacteria from invading the body, therefore its development is believed to be directly associated with the immune function of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of increase of HCW by CB is consistent with the increased LWBS. The increase in LWBS with CB in this study may be due to the fact that the CB can provide metabolites, especially short-chain FA, as an energy source to the digestive enzyme system, thus increase the BW [ 15 ]. The spleen is the largest immune organ in animal body, which can improve the body resistibility and minimize the pathogenic bacteria from invading the body, therefore its development is believed to be directly associated with the immune function of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, butyric acid produced by CB metabolism can regulate muscle lipid metabolism [ 14 ]. Furthermore, the inconclusive effects of CB in the literature may be due to differences in source of CB strains used, its supplemental dose and type of diet [ 15 , 16 ]. Zhang et al [ 17 ] observed an interaction between dietary lipids and CB on lipid-related gene expression in breast muscle of broiler chickens, suggesting that dietary fat may be interacted with CB on meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…An increased F:B ratio has been shown to contribute to improved bovine performance, including body weight gain and milk fat yield [ 29 ], but there are contradictory reports [ 30 ]. A greater abundance of Firmicutes indicates a more feed-efficient animal [ 21 , 31 ] with improved structural polysaccharide degradation [ 32 ]. Changes in this ratio did not affect digestibility, and we could not assess its effect on production parameters, because the animals in our study were dry cows [ 14 ].…”
Section: Discussionmentioning
confidence: 99%